Analysing the online wine tourism strategies of American and Italian wineries. (2017) - Simeon, Roblyn; Sayeed, Lutfus; Onetti, Alberto; Talaia, Marco
As competition intensifies in the global wine market, online wine tourism has become a crucial marketing dimension for wineries and wine regions around the world. This paper presents and extends the proven attracting, informing, positioning and delivering framework for examining the strategic orientation of winery websites. Two nations that are at the forefront of the competition between old world and new world wines are the USA and Italy. Qualitative and quantitative analyses showed that American wineries were generally better at projecting a wide-range virtual branding characteristics. Italian wineries were better at the attracting dimension, and they focused mainly on local characteristics.